Analysis of Public Perceptions Towards Layer Chicken Farm: Insight from Sumarambu Subdistrict, Indonesia - Zalzabila, Andi Muhammad Alif; Tenrisanna, Vidyahwati; Ridwan, Muh; Kasim, Kasmiyati (Tarjih : Agribusiness Development Journal, 2025)
This study investigated community perceptions towards the presence of a layer chicken farm in Sumarambu Subdistrict, Telluwanua District, Palopo City, Indonesia. A descriptive quantitative survey was conducted on 40 households within a 500-meter radius of the farm, categorized into three zones based on proximity. Perceptions were measured across environmental, economic, and social aspects using a Likert scale. The results showed that the community agreed the farm had negative environmental impacts, such as strong odour and poor waste management, with perceptions varying significantly by proximity. From an economic perspective, residents noted advantages, including reduced egg prices and increased consumption. Nonetheless, perceptions were consistent across different areas, suggesting that the farm acts as an economic enclave with minimal integration into the broader community. From a social perspective, the community demonstrated differing opinions regarding the positive impacts on employment, social assistance, and compensation, with no significant spatial variations. This highlights a lack of social responsibility initiatives. The Kruskal-Wallis test revealed substantial differences in environmental perceptions among zones for odour and waste, but not for water pollution and cleanliness. No significant zonal differences were found for economic and social aspects. This study emphasizes the importance of understanding and integrating community perceptions into sustainable livestock development to ensure alignment with local needs, values, and expectations.